Synthesis of Some New 1,2,4-Triazoles Derived from 2-Mercaptobenzimidazole (Baghdad Science Journal, 2009)
New 1,2,4-triazole derivatives of 2-mercaptobenzimidazole (MB) are reported. Ethyl (benzimidazole-2-yl thio) acetate (1) has been prepared by condensing 2-mercaptobenzimidazole with ethylchloroacetate. The ester (1) on reacting with hydrazine hydrate gave the corresponding acetohydrazide(2)which was reacted separately with phenylisocyanate and phenylisothiocyanate, followed by ring closure in an alkaline medium giving 3-[(benzimidazole-2-yl thio) methyl]-4-phenyl-1,2,4-triazole-5-ol and 3-[(benzimidazole-2-yl thio) methyl]-4-phenyl-1,2,4-triazole-5-thiol respectively (6,7). Reaction of acetohydrazide (2) with CS2 and ethanol/KOH, gave dithiocarbazate salt (8). Cyclization of (8) with hydrazine hydrate gave 3-[(benzimidazole-2-yl thio) methyl]-4-amino-1,2,4-triazole-5-thiol (9). Furthermore, new Schiff bases (3a-e) were prepared through the reaction of the acetohydrazide (2) with aromatic aldehydres. The prepared compounds were identified by spectral methods FTIR, UV. Measurements of some physical properties and some specific reactions, were carried out.